2020
DOI: 10.1108/ijm-08-2018-0281
|View full text |Cite
|
Sign up to set email alerts
|

Employee turnover intentions and job performance from a planned change: the effects of an organizational learning culture and job satisfaction

Abstract: PurposeIn the face of a changing and turbulent environment, an organizational learning culture (OLC) is crucial for the long-term operation of an organization. A learning culture provides the capacity to effectively integrate employees, and it also provides structure so that an organization can move forward via continuous learning and change. Few empirical results are available from Chinese companies enduring an organizational change. To bridge this research gap, this study investigated the relationships among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 43 publications
8
104
0
6
Order By: Relevance
“…Research findings report a positive relationship between leadership behavior and job satisfaction [36]. When leaders are careful to help and support employees who are contacted and concerned about their needs, they will feel more satisfied [37]; [38]. Such supportive leader behavior has been found to be associated with employee job satisfaction [39].…”
Section: Management Leadershipmentioning
confidence: 99%
“…Research findings report a positive relationship between leadership behavior and job satisfaction [36]. When leaders are careful to help and support employees who are contacted and concerned about their needs, they will feel more satisfied [37]; [38]. Such supportive leader behavior has been found to be associated with employee job satisfaction [39].…”
Section: Management Leadershipmentioning
confidence: 99%
“…Previous research suggests that job satisfaction relates negatively with turnover intention in a meta-analysis of the turnover literature [64], [65,46,66]. Randhawa, [64] reported that job satisfaction was a significant negative correlate of turnover intention among agricultural scientists in India.…”
Section: Job Satisfaction and Turnover Intentionsmentioning
confidence: 99%
“…Career satisfaction is an essential indicator of employee turnover intention. Employees who have high career satisfaction tend to stay in the organization and not leave their organization (Lin & Huang, 2020). Thus, organizations must make more extraordinary efforts to understand better and improve career satisfaction to reduce employee turnover intention (Direnzo & Greenhaus, 2011).…”
Section: Career Satisfaction (Cs) and Turnover Intention (Ti)mentioning
confidence: 99%